A8.28 Depletion of autoantibody-secreting plasma cells based on the specificity of the secreted antibody. (13th February 2015) - Taddeo, A; Hoyer, BF; Gerl, V; Chang, HD; Pelz, A; Kohler, S; Radbruch, A; Hiepe, F
Abstract : Background and objectives: Long-lived plasma cells (LLPCs) producing pathogenic antibodies are an important factor in autoimmune diseases maintenance and relapse. The therapeutic options available so far for targeting these cells (e.g. autologous stem cell transplantation, bortezomib) have the major disadvantage of eliminating the protective humoral immunity with the obvious caveats regarding a higher risk of infection. Therefore the development of new therapeutic tools for the selective depletion of LLPCs secreting pathogenic antibodies would be a great step forward. Material and methods: We synthetized an antigen affinity matrix (AM) conjugating a plasma cell specific antibody (i.e. anti-CD138) with the antigen/autoantigen-of-interest (i.e. Ovalbumin or Acetylcholine-Receptor, AChR). We performed proof-of-concept experiments using the anti-CD138-ovalbumin using: 1) anti-ovalbumin secreting hybridoma cells and 2) spleen cells from ovalbumin-immunised mice. Moreover, we used the anti-CD138-AChR AM for the ex-vivo depletion of splenic pathogenic plasma cells isolated from mice with experimental autoimmune myasthenia gravis (EAMG). Results: Antibodies secreted by ovalbumin-specific plasma cells could bind the ovalbumin delivered at surface of the plasma cell by the AM. In this way, anti-ovalbumin-specific hybridoma cells and splenic plasma cells were induced to commit suicide in presence of complement. Conversely, unrelated plasma cells (i.e. secreting antibodies against other antigens) were not lysed confirming the specificity of the method. Importantly, pathogenic plasma cells secreting anti-AChR-autoantibodies from the spleen of mice with EAMG can be eliminated using an anti-CD138-AChR-construct, suggesting that the AM technology can be used for the specific depletion of autoantibodies secreting plasma cells. Conclusion: Here we show that the AM technology could represent the first available tool for the depletion of (auto)antigen-specific plasma cells without affecting the protective plasma cells. We are currently testing the therapeutic efficacy of this AM in murine models of autoimmune disease.